2016
DOI: 10.18632/oncotarget.10390
|View full text |Cite
|
Sign up to set email alerts
|

Smac mimetic induces cell death in a large proportion of primary acute myeloid leukemia samples, which correlates with defined molecular markers

Abstract: Apoptosis is deregulated in most, if not all, cancers, including hematological malignancies. Smac mimetics that antagonize Inhibitor of Apoptosis (IAP) proteins have so far largely been investigated in acute myeloid leukemia (AML) cell lines; however, little is yet known on the therapeutic potential of Smac mimetics in primary AML samples. In this study, we therefore investigated the antileukemic activity of the Smac mimetic BV6 in diagnostic samples of 67 adult AML patients and correlated the response to clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 53 publications
1
9
0
1
Order By: Relevance
“…HTRA4 was detect as extremely high up methylated in TSS as well as in gene body regions. It is confirmed to be tumor suppressor gene and consider as biomarker in other cancers [ 34 ]. It was also described as down regulated in AML.…”
Section: Resultsmentioning
confidence: 99%
“…HTRA4 was detect as extremely high up methylated in TSS as well as in gene body regions. It is confirmed to be tumor suppressor gene and consider as biomarker in other cancers [ 34 ]. It was also described as down regulated in AML.…”
Section: Resultsmentioning
confidence: 99%
“…SMAC mimetics represent a group of engineered analogues of SMAC for pharmacological use that work in a similar manner to native SMAC, inducing cell death. Preclinical studies have shown that SMAC mimetics induce cell death in a large proportion of primary AML samples: 51% of cases are clearly sensitive; 21% are moderately sensitive and 28% are resistant [310]. Interestingly, most of AML samples resistant to Ara-C, are sensitive to the SMAC mimetic BV6 [310].…”
Section: The Extrinsic Apoptotic Pathway: Trail-rs Caspase-8 and mentioning
confidence: 99%
“…Preclinical studies have shown that SMAC mimetics induce cell death in a large proportion of primary AML samples: 51% of cases are clearly sensitive; 21% are moderately sensitive and 28% are resistant [310]. Interestingly, most of AML samples resistant to Ara-C, are sensitive to the SMAC mimetic BV6 [310]. Sensitivity of AML blasts to SMAC mimetic correlated with low XIAP expression and presence of NPM1 mutations [310].…”
Section: The Extrinsic Apoptotic Pathway: Trail-rs Caspase-8 and mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several studies reported an overexpression of IAP proteins in AML cells which is associated with poor prognosis . Furthermore, a number of recent reports pointed out the importance of using SMAC mimetics in AML cells to promote induction of cell death pathways …”
Section: Introductionmentioning
confidence: 99%